AN APPRAISAL OF THE MORALITY OF ABORTION IN JOHN HICK’S ETHICS - Udoeka, Oto-Obong John; Udofia Christopher (Journals Park Publishing, 2022)
This research examines the morality of abortion in John Hick’s ethics. There exists a recurrent knowledge cum research gap on the question of the morality of abortion. This research exercise addresses this lacuna by interrogating the phenomenon of abortion from the perspective of the moral citations of John Hick. Consequently, the cardinal objective of this essay is to appraise the morality of abortion in line with Hick’s ethics in order to establish whether the act of abortion is right or wrong. The philosophical methods of exposition, analysis and criticism were utilized in the conduct of this research. John Hick’s ethics was adopted as the framework for this study. The paper discovered that Hick frowns at induced abortion and sees it as an aberration despite the fact that every human has the freedom to choose either what is right or wrong. The study concludes that abortion is necessary if and only if it threatens the life of the mother.
Keywords: Morality; Abortion; Woman